PERSEPSI SISWA TERHADAP PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS XI MIA2 MAN 1 PEKANBARU - Angriani, Fitri; Zulfarina, Zulfarina; Syafi?i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to study students' perceptions of the application of the Discovery Learning model in class XI MIA2 MAN 1 Pekanbaru. The research was carried out from August until October 2019. Parameter of this research is student's perception toward applying Discovery Learning model with 6 indicators that are: attention, expectation, motivation, need, value system, and personality type. The data collected was analyzed using SPSS version 23.00 for windows. The results of the data analysis showed that students' perceptions of attention indicators received a value of 3.88, an expectation indicator of 3.83, a motivational indicator of 3.76, a need indicator of 3.8, a system indicator of a value of 3.85, and a personality indicator of 3.76. Overall students' perceptions of the application of the Discovery Learning model are good with a score of 3.81.Key Words: Perception, Discovery Learning model